The Effect of Lemon, Watermelon, and Cucumber Infused Water to Decrease Blood Pressure - Fandizal, Muhammad; Sani, Dhien Novita; Astuti, Yuli (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2020)
Introduction: Hypertension "The Silent Killer" is a serious medical condition that can increase the risk of heart, brain, and kidney disease. The preventive role of nurses in clients with uncontrolled hypertension to overcome complications can be done by adopting a healthy lifestyle. A healthy lifestyle can be given infused water therapy with cucumber, lemon, and watermelon. Objective: The purpose of this study was to analyze the effect of lemon, watermelon, and cucumber-infused water on reducing blood pressure in clients with hypertension. Method: This study used a Quasi Experiment design with a Nonequivalent Control Group design. Sampling using a purposive sampling technique. Hypothesis testing is used with two different tests mean independent sample t-test and dependent sample t-test. Results: There were differences before and after the intervention of Lemon, Watermelon, and Cucumber Infused Water to reduce blood pressure in clients with hypertension (ρ 0.030; 0.000; 0.000 <0.05). Conclusion: Consumption of infused water of lemon, watermelon, and cucumber can lower blood pressure. Of the three ingredients, the highest blood pressure reduction was used cucumber-infused water.